Effective Strategies for Identifying, Nurturing, and Retaining Future Leaders - Lestari, Gita (Yayasan Pendidikan Bukhari Dwi Muslim, 2023)
Purpose: This study explores the critical processes of identifying, nurturing, and retaining future leaders within organizations. It aims to enhance leadership development programs by offering theoretical advancements and practical insights. Research Design and Methodology: Employing a qualitative research design, the study synthesizes existing literature on leadership development. It employs detailed thematic analysis and coding of scholarly articles, books, and empirical studies to understand the nuances of leadership strategies. Findings and Discussion: Findings reveal the need for a holistic approach to leadership development, encompassing assessments of cognitive and emotional intelligence, tailored developmental interventions, mentorship, and the alignment of organizational values with individual career goals. Key themes include the importance of emotional intelligence, mentorship, and the impact of organizational culture on leadership retention. Implications: The research underscores the necessity for organizations to implement adaptive and personalized leadership development strategies that respond to changing business landscapes. It advocates for integrating innovative tools such as big data analytics and AI into leadership assessments and emphasizes creating a supportive work environment that fosters long-term commitment among leaders, essential for maintaining a competitive edge.